Analisis Uji Pengaruh Karakteristik Pekerjaan, Kepuasan Kerja Karyawan dan Budaya Organisasi Terhadap Komitmen Organisasi pada Perusahaan Logistik Pelabuhan - Devi, Yesica N; Akseptori, Ristanti; Hardiyanti, Fitri (Akuntansi dan Manajemen, 2024)
Getting skilled human resources is not easy because of the increasingly tight competition, so it requires commitment for the company. In a port logistics company in Surabaya, there was a decrease in the number of employees due to early retirement. In addition, the increase in the number of management work plans caused an unbalanced workload. So that it causes work stress in employees. This study aims to analyze the influence of job characteristics, employee job satisfaction, and organizational culture on organizational commitment in a port logistics company in Surabaya. This study used a multiple linear regression analysis method with the help of SPSS 26. The number of respondents was 81 company employees. The results of this study indicate that job characteristics, job satisfaction, and organizational culture have a positive and significant effect on organizational commitment both partially and simultaneously. The coefficient of determination (R2) produced is 0.521, which means that the independent variable explains 52.1% of the variability of organizational commitment, while the remaining 47.9% is influenced by other variables outside this study. So it can be concluded that in this study there is an increase in job characteristics that are in accordance with employee abilities, high job satisfaction, and a supportive organizational culture can increase organizational commitment.